2003
DOI: 10.1038/ng1261
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous mutations of the kinesin KIF21A in congenital fibrosis of the extraocular muscles type 1 (CFEOM1)

Abstract: Congenital fibrosis of the extraocular muscles type 1 (CFEOM1; OMIM #135700) is an autosomal dominant strabismus disorder associated with defects of the oculomotor nerve. We show that individuals with CFEOM1 harbor heterozygous missense mutations in a kinesin motor protein encoded by KIF21A. We identified six different mutations in 44 of 45 probands. The primary mutational hotspots are in the stalk domain, highlighting an important new role for KIF21A and its stalk in the formation of the oculomotor axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
197
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 238 publications
(210 citation statements)
references
References 13 publications
3
197
0
3
Order By: Relevance
“…Among the six genes deleted in Case 1 only, KIF21A is known to be mutated in patients with CFEOM type 1 (CFEOM1, OMIM #135700) (Yamada et al 2003). Thus, CFEOM observed in Case 1 may be accounted for by the lack of KIF21A due to the deletion.…”
Section: Resultsmentioning
confidence: 99%
“…Among the six genes deleted in Case 1 only, KIF21A is known to be mutated in patients with CFEOM type 1 (CFEOM1, OMIM #135700) (Yamada et al 2003). Thus, CFEOM observed in Case 1 may be accounted for by the lack of KIF21A due to the deletion.…”
Section: Resultsmentioning
confidence: 99%
“…The amplicons were subjected to analysis by denaturing high-performance liquid chromatography (DHPLC) using a nucleic acid fragment analysis system (WAVE; Transgenomic, Inc., Omaha, NE) and/or to direct DNA sequencing on an ABI 377 DNA sequencer (Applied Biosystems, Foster City, CA) as previously described. 7 The PCR sequencing and DHPLC primers and conditions are available on request. The three PHOX2A exons and flanking intron-exon boundaries were similarly amplified using our published primer sets 10 and these amplicons were directly sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that in most pedigrees CFEOM1 maps to the FEOM1 locus on chromosome 12cen, [3][4][5][6] and results from recurrent heterozygous mutations in a developmental kinesin, KIF21A. 7 Similar to other members of the kinesin superfamily, mouse Kif21a is a motor protein engaged in anterograde axonal transport. 8 We have identified six different pathogenic KIF21A mutations in 44 (98%) of 45 CFEOM1 probands.…”
mentioning
confidence: 99%
“…15 KIF21A gene mutations have been identified in patients with CFEOM type 1, which shows an autosomal dominant trait and is associated with the absence of the superior branch of the oculomotor nerve. 16 ARIX (PHOX2A) gene mutations have been found in patients with CFEOM type 2, which shows an autosomal recessive trait and is proposed to result from aberrant development of the oculomotor and trochlear nerve, and nuclei in the brainstem. 17 On the basis of working hypothesis that idiopathic superior oblique muscle palsy might be a clinically milder variant of CFEOM type 2, we previously analyzed ARIX and PHOX2B gene polymorphisms in patients with idiopathic superior oblique muscle palsy.…”
Section: Introductionmentioning
confidence: 99%